Application of analytical hierarchy process (AHP) in prioritizing HAZOP analysis for pilot plant (Chemical Engineering Research Bulletin, 2017)
Injuries, accidents or even fatalities while working in pilot plant are reported worldwide. The implementation of process hazards analysis (PHA) in pilot plant is expected to further reduce the risks of accidents. Hazard and operability (HAZOP) analysis is one of the most widely used methods for PHA. Generally, the outcome of HAZOP analysis could results in identifying large number of hazards thus poses a challenge for assessors to take actions in dealing with all the hazards. The common practice in prioritizing the critical hazards is based on assessors experience through deductive judgment using rating scale, taking into consideration safety and the associated costs. However the novel operations and process used, unproven or changing technology, and lack of safety information due to developmental stages have led to poor hazards prioritization and difficulty in selecting actions. This paper presents an application of analytical hierarchy process (AHP) in prioritizing HAZOP analysis for pilot plant. Through this approach, the significant hazards identified using HAZOP will be quantitatively weighted and ranked based on their priority along with the appropriate counter measures to be taken. Application of this approach at the high pressure CO2-hydrocarbon absorption system pilot plants as case study showed that the proposed methodology is capable of identifying and ranking the significant hazards in the process following HAZOP analysis. This is particularly useful as a leading indicator to process designers/engineers/researcher in prioritizing their efforts and resources on more significant hazards, hence prevent accidents of the pilot plant.Chemical Engineering Research Bulletin 19(2017) 87-95